1997
DOI: 10.1111/j.1365-3156.1997.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight distribution in rural North‐West Burkina Faso

Abstract: SummaryTwo thousand and twenty-six delivery records from 1987 to 1989 in 5 rural health units in North Western Burkina Faso were analysed. The mean birthweight was 2899 g, with an overall incidence of low birthweight of 9.3%. Increasing birth order from I to 3 was associated with increasing birthweight; for birth orders ' 3 , birthweight was relatively constant. There is a marked seasonal variation in birthweight, with a decrease in the rainy season and an increase during the dry season. These findings are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In France, data were collected in spring and autumn in the late 1980s, and no differences were found between the two periods 21 . Seasonal variations in birthweight have been reported in rural areas of tropical countries, possibly related to food supply, work load and malaria 22–24 . In other countries, a few studies have shown variations in preterm delivery rates and the distribution of GA according to calendar month 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…In France, data were collected in spring and autumn in the late 1980s, and no differences were found between the two periods 21 . Seasonal variations in birthweight have been reported in rural areas of tropical countries, possibly related to food supply, work load and malaria 22–24 . In other countries, a few studies have shown variations in preterm delivery rates and the distribution of GA according to calendar month 25–27 .…”
Section: Discussionmentioning
confidence: 99%